Non-invasive pressure measurement based on magneto-mechanical effects. (14th August 2018) - Zeng, Zhoumo; Zhao, Chengwu; Huang, Xinjing; Li, Jian; Chen, Shili
Abstract: This paper proposes and experimentally demonstrates a non-invasive pressure measurement method based on magneto-mechanical effects. The relative permeability–stress curve is obtained using the J – A force magnetic coupling model, then imported into a finite element simulation model based on the coupled multiphysics of mechanical mechanics and static magnetics. The magnetic variations versus the pressure changes at the periphery of a pressure vessel are obtained through simulations and multi-channel magnetic measurement experiments. The proposed method shows good linearity in the range of 0–3 MPa, and is more sensitive for smaller, thinner vessels. Overrange measurement can lead to saturation. Measurement points need to be carefully chosen in order to achieve the highest sensitivity and precision. The highest sensitivity achieved is 1.314, and the readily available sensitivity is about 5.0 . The precision in many cases is better than 0.1 MPa. The repeatability errors for the three components are about 2.7% of the full scale when referred to the most sensitive component. The measurement fluctuation over 48 h is 0.1 MPa when referred to the readily available sensitivity.